A REVIEW STUDY ON HYDROGEN EMBRITTLEMENT OF STEEL - Anastasovska, Elena; Doncheva, Elisaveta; Zdraveski, Filip (Society for Structural Integrity and Life and IMS Institute, 2024)
A common and intricate phenomenon known as hydrogen embrittlement of steel is the deterioration of the mechanical properties of metal in relation to stress corrosion cracking. This phenomenon has been extensively studied, with numer-ous works proposed over the last two decades, but there is still a lack of unified solutions and a solid understanding of the phenomenon. The purpose of this paper is to provide a review of the literature and publications on hydrogen embrittlement in steel. It focuses on recent developments and methods that have contributed to a better understand-ing of the relationship between steel structure, properties, and performance, with a particular emphasis on hydrogen diffusion, characterisation, mechanisms, and prevention of hydrogen embrittlement in structural steel. Furthermore, the paper discusses recent advances in experimental and multi-scale modelling and proposes future studies to address challenges related to hydrogen embrittlement in steels.
Keywords: hydrogen embrittlement,diffusion,hydrogen embrittlement mechanism,preventions